Pergeseran Mata Pencaharian Pada Generasi Muda Petani Di Desa Selopanggung Kabupaten Kediri - Ningtyas, Trimurti; Kurnia, Aminatul (Prodi Sosiologi Agama, 2021)
Indonesia as an agrarian country because most of the Indonesian people make a living as farmers. In Selopanggung Village, located on the slopes of Mount Wilis, the younger generation has also experienced a decline in interest in farming. This study aims to describe how the shift in people's livelihoods from farmers to other livelihoods. This study uses a qualitative method with descriptive analysis. The theory used is social action from Max Weber as an analysis of actions that affect the shift in the livelihoods of the younger generation of farmers in Selopanggung Village. The results in this study describe how the actions of the younger generation choose not to become farmers, so that it can be identified what factors can influence these actions. The findings are that there are four actions that can be identified in shifting livelihoods, as well as four factors that can support these actions.